2021
DOI: 10.3390/ma15010166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-SiO2 on the Microstructure and Mechanical Properties of Concrete under High Temperature Conditions

Abstract: The aim of the research was to determine how the admixture of nanosilica affects the structure and mechanical performance of cement concrete exposed to high temperatures (200, 400, 600, and 800 °C). The structural tests were carried out on the cement paste and concrete using the methods of thermogravimetric analysis, mercury porosimetry, and scanning electron microscopy. The results show that despite the growth of the cement matrix’s total porosity with an increasing amount of nanosilica, the resistance to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The use of liquid nanomaterials, meaning as mixing water with micro-nano bubbles, is quite a novel approach in the recent scientific research [33,36,83,84]. Most of the scientists used nanomaterials in the solid form [85][86][87] or colloids [40,[87][88][89][90][91]. In a paper where the impact of hydrogen micro-nano bubbles on the microstructure of cement-based material were investigated (e.g., [34]), the authors observed a significant change in pore size distribution, which did not occur in the case of the presented results for micro-nano oxygen and ozone bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…The use of liquid nanomaterials, meaning as mixing water with micro-nano bubbles, is quite a novel approach in the recent scientific research [33,36,83,84]. Most of the scientists used nanomaterials in the solid form [85][86][87] or colloids [40,[87][88][89][90][91]. In a paper where the impact of hydrogen micro-nano bubbles on the microstructure of cement-based material were investigated (e.g., [34]), the authors observed a significant change in pore size distribution, which did not occur in the case of the presented results for micro-nano oxygen and ozone bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows the compressive and tensile strength losses of concrete at 600 °C. Brzozowski et al [68] reported that the thermal resistance enhancement with nanosilica was attributed to its thermal characteristics as well as the cement paste porosity structure when they used a method that was good at dispersing the nanoparticles in Brzozowski et al [68] reported that the thermal resistance enhancement with nanosilica was attributed to its thermal characteristics as well as the cement paste porosity structure when they used a method that was good at dispersing the nanoparticles in concrete. It was reported that the 0.3-300 m diameter pores were reduced with nanosilica particles, which also limited the microcracks and strengthened the ITZ zone.…”
Section: Residual Mechanical Strength Improvements With Nanomaterialsmentioning
confidence: 99%
“…Based on the results, an ideal nano-SiO2 content improved the thermal resistance. Brzozowsk et al [20] found that nanoparticles enhanced the behavior of concrete at high temperatures in cement mortar containing quartz and magnetite aggregates. Researchers [21][22][23][24] found that adding 4% of nano-SiO2 by replacing it with cement improved compressive strength, and whenever it exceeded 4%, its positive effect decreased.…”
Section: Introductionmentioning
confidence: 99%